Molecular and virulence profiling of Aeromonas veronii from diseased Nile tilapia in Central Java, Indonesia - DINI SISWANI MULIA; ZAHROTUN NISA; SUWARSITO SUWARSITO; CAHYONO PURBOMARTONO; OLGA OLGA; BOBY MUSLIMIN; AGUS SETYAWAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Mulia DS, Nisa Z, Suwarsito, Purbomartono C, Olga, Muslimin B, Setyawan A. 2025. Molecular and virulence profiling of Aeromonas veronii from diseased Nile tilapia in Central Java, Indonesia. Biodiversitas 26: 3647-3657. Nile tilapia (Oreochromis niloticus (Linnaeus, 1758)) is a widely cultivated species with promising economic potential; however, bacterial infections pose a significant barrier to successful production. Molecular characterization is essential for accurately identifying pathogenic bacteria involved in disease outbreaks. This study aimed to determine the molecular and virulence of Aeromonas veronii isolated from diseased Nile tilapia in Central Java, Indonesia. Diseased fish were collected using a purposive sampling technique. Molecular identification was conducted using markers for 16S rRNA, gyrB, and ten virulence-associated genes, including aerA/haem, alt, ast, act, flaA, lafA, fstA, ahp, ela, and lip. Antibiotic susceptibility testing was performed using eight antibiotics: bacitracin (10 µg), penicillin (10 µg), amoxicillin (25 µg), ciprofloxacin (5 µg), vancomycin (30 µg), clindamycin (2 µg), tetracycline (30 µg), and chloramphenicol (30 µg). Results revealed that seven isolates were identified as A. veronii. All isolates (100%) harbored two significant virulence genes, aerA/haem and ela, while none of the isolates (0%) tested positive for the other eight virulence genes. The consistent presence of these two virulence factors suggests a high pathogenic potential of the isolates. Antibiotic susceptibility assays indicated that all isolates (100%) were resistant to bacitracin, penicillin, amoxicillin, vancomycin, and clindamycin, but remained sensitive to ciprofloxacin, tetracycline, and chloramphenicol. In conclusion, the present findings support the implementation of targeted diagnostic approaches for A. veronii infections. Detecting key virulence factors and multidrug resistance in A. veronii highlights its potential as a significant threat to aquatic animal health. Consequently, there is an urgent need to strengthen biosecurity measures, including routine microbial monitoring, judicious and responsible use of antibiotics, and improved environmental management practices. Furthermore, developing alternative strategies, such as vaccination, represents a proactive and sustainable long-term solution to enhance the resilience of aquaculture systems.